Introduction to the Special Issue on Modelling Processes of Comprehension, Aesthetic Experience, and Interpretation in Literary Conversations - Carl, Mark-Oliver (L1-Educational Studies in Language and Literature, 2023)
This introduction briefly outlines developments in research on literary conversations in classrooms and other educational settings and explains why empirical studies looking into relations between mental processes of literary reception on the one hand side and communicative behaviour on the other hand side must (also) draw on methods beyond conversation analysis. It then proceeds to give a quick overview of the seven contributions to this Special Issue, and concludes with remarks on directions for future research in this field.